2021
DOI: 10.1016/j.plabm.2021.e00231
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal hemoglobin affects the accuracy of whole blood bilirubin measurement on GEM Premier 4000 blood gas analyzers

Abstract: Objectives Whole blood bilirubin measured on blood gas analyzers is accepted by physicians in neonatal hyperbilirubinemia management since it requires a small sample volume. The accuracy of bilirubin measurement on blood gas analyzers is instrument dependent and remains controversial. Design and Methods Bilirubin in adult and umbilical cord whole blood samples, spiked with an unconjugated bilirubin standard, and non-spiked adult plasma samples was measured on a blood ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Unfortunately, the reliability of hemoglobin measurement using a blood gas analyzer remains controversial (12,13). Huang et al (14) found that hemoglobin measurements using a GEM 4000 blood gas analyzer is consistent with the hematology analyzer results in adults, but a significant bias is using neonatal blood. In line with Huang's study, an experience from an NICU in Australia demonstrated that blood gas analyzer (Radiometer ABL 800 flex) results for neonatal bilirubin should be corrected according to fetal hemoglobin (HbF) values rather than adult hemoglobin measurements (15).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the reliability of hemoglobin measurement using a blood gas analyzer remains controversial (12,13). Huang et al (14) found that hemoglobin measurements using a GEM 4000 blood gas analyzer is consistent with the hematology analyzer results in adults, but a significant bias is using neonatal blood. In line with Huang's study, an experience from an NICU in Australia demonstrated that blood gas analyzer (Radiometer ABL 800 flex) results for neonatal bilirubin should be corrected according to fetal hemoglobin (HbF) values rather than adult hemoglobin measurements (15).…”
Section: Discussionmentioning
confidence: 99%
“…Low hemoglobin levels have been independently linked to mortality, cardiovascular events, and major bleeds in individuals with stable coronary artery disease, signifying the prognostic value of hemoglobin and its derivatives in cardiovascular health (Kalra et al, 2017 ). The determination of hemoglobin derivatives through spectrophotometric and multi-component spectrophotometric analysis provides essential insights into the biochemical pathways influencing cardiovascular disease and its outcomes (Kaewprayoon et al, 2020;Huang et al, 2021;Attia et al, 2015) Therefore, this study aims to unravel the complex interplay between electrolytes, vitamin D, and hemoglobin derivatives, shedding light on the multifaceted mechanisms underpinning cardiovascular health and disease. Understanding these intricate relationships offers a promising avenue for developing more effective strategies to combat cardiovascular diseases, enhancing patient care and outcomes in this critically important area of medical research.…”
Section: -Introductionmentioning
confidence: 99%